(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores a variety of techniques that can effectively improve speakingskills in language learners. It discusses the importance of active interaction, personalized learning, the role of real-life language exposure, and the use of digital tools. The article also highlights the impact of confidence-building strategies, pronunciation training, and structured practice tasks. The purpose is to provide language educators with applicable methods to enhance learners’ oral communication in academic and everyday contexts.